Elevating Mongolia-Türkiye Relations to a Strategic Partnership: Insights from Political Cooperation - Khishgee, Selenge (Mongolian Journal of International Affairs, 2024)
This study explores the potential for advancing Mongolia-Türkiye relations to the level of "Strategic Partnership" through a detailed examination of political interactions. Since the establishment of diplomatic ties in 1969, the relationship between the two countries has been characterized by high-level political visits, economic cooperation, and cultural exchanges. Despite these positive developments, there remains a significant gap in research concerning the mechanisms and strategies necessary to elevate the partnership to a fully-fledged strategic level. The article examines the key drivers of this evolving relationship, including diplomatic missions, mutual cultural interests, with a particular focus on high-level visits and their impact on the bilateral relationship. Through a review of historical milestones, and diplomatic engagements, this study offers insights into the current state of the partnership, challenges such as trade imbalances and economic dependence, and opportunities for future cooperation. Ultimately, the study concludes that the Mongolia-Türkiye relationship holds significant potential for advancement to a Strategic Partnership. By building on past achievements and leveraging shared cultural ties, trade, and tourism, the relationship could be strengthened, offering long-term mutual benefits for both nations.